(untitled) (Indonesian Journal of Agrarian Law, 2026)
The practice of private land sales and purchases based on receipts still occurs in society and raises issues regarding legal certainty regarding land ownership. This study aims to analyze the practice of private land sales and purchases in Bambankerep Village and its implications for legal certainty. This study employs an empirical legal methodology through a literature review of legislation and legal literature, as well as interviews with village officials and legal practitioners to obtain empirical data. The results indicate that the community still opts for informal transactions due to economic factors, procedural ease, and trust in local officials, even though such transactions are supported only by simple documents like receipts that lack legal standing as a basis for the transfer of rights. Consequently, buyers are in a legally vulnerable position and are prone to disputes. This study underscores the importance of using PPAT deeds and land registration to ensure legal certainty and provide legal protection for the parties involved in land transactions.